Prevalence of vitamin D deficiency and effect of vitamin D supplementation on feto-maternal outcome in tertiary care centre - Yadav, Munmun; Verma, Mahendra Kumar; Bairwa, Mohan; Meena, Govardhan; Rajoria, Lata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Vitamin D deficiency is widely prevalent throughout the world. Pregnant women, neonates and infants form most vulnerable groups for vitamin D deficiency. Hypovitaminosis D in pregnancy has been reported to cause various fetomaternal effect, i.e. increased risk of preeclampsia (PE), gestational diabetes mellitus (GDM), caesarean section, hypocalcemia, subclinical myopathy, neonatal tetany, hyperbilirubinemia congenital rickets and infantile rickets, etc. Only few Indian studies are available in this regard. The objectives are to find prevalence of vitamin D deficiency in pregnant women and to evaluate the effect of supplementation with cholecalciferol in improving vitamin D levels in pregnant women and evaluate its correlation with feto-maternal outcome. Methods: A prospective observational was conducted on 120 Pregnant women on their first visit to hospital irrespective of gestational age were offered the test and on the basis of inclusion and exclusion criteria are included in study and vitamin D level was done to know the prevalence of vitamin D deficiency. Apart from routine obstetrical investigation, serum vitamin D (total) level was estimated. All results were recorded and analyzed statically. Results: Out of 120 patients 101 (84.1%) were found to be vitamin D deficient. Mean age of vitamin D deficient group was 28.31±3.86 and sufficient group was 26.37±2.83.81 (67.5%) were vegetarian and 39 (32.5%) were nonvegetarian.75 (92.59%) vegetarian and 26 (66.66%) non-vegetarian found to be vitamin D deficient. (p<0.05). Vitamin D supplementation has been observed to reduce risk of preeclampsia. (p<0.05) and vitamin D sufficiency associated with reduced risk of low birth weight babies. Conclusions: Vitamin D supplementation reduces risk of maternal comorbidities and helps improve neonatal outcomes.